2019
DOI: 10.1021/acs.jpca.8b12323
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission of Iodide from Aqueous Aerosol Particle Surfaces

Abstract: The photoemission of iodide from aqueous aerosol particle surfaces measures the surface concentration of iodide in predominantly supersaturated NaCl aerosol particles. Using the Langmuir model to describe the adsorption to the surface of aqueous iodide anions, the standard Gibbs free energy of adsorption is −15 kJ/mol in these systems. The presence of charged surfactants on the particle surfaces changes the adsorption behavior of iodide. The addition of sodium docecylsulfate (SDS) reduces the coverage of iodid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(96 reference statements)
2
14
0
Order By: Relevance
“…26 Recently, we used the photoemission yield of iodide to study the anion's affinity for the water−air interface in a supersaturated aerosol. 27 The results demonstrate preferential detection of interfacial species, consistent with an estimated electron attenuation length in water of 1 to 3 nm 28−32 at the energies of this experiment. Our goal in this paper is to use this methodology to monitor short-lived transient species, such as the triplet states of photosensitizer molecules, and to measure the initial stage kinetics.…”
Section: ■ Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…26 Recently, we used the photoemission yield of iodide to study the anion's affinity for the water−air interface in a supersaturated aerosol. 27 The results demonstrate preferential detection of interfacial species, consistent with an estimated electron attenuation length in water of 1 to 3 nm 28−32 at the energies of this experiment. Our goal in this paper is to use this methodology to monitor short-lived transient species, such as the triplet states of photosensitizer molecules, and to measure the initial stage kinetics.…”
Section: ■ Introductionsupporting
confidence: 81%
“…Our analysis assumes that the response is linear with concentration, as we have found for low concentrations of photoemitters in previous studies. 27,38 We collect transient lifetime data by monitoring the aerosol electrometer signal as a function of the delay between the excitation and photoemission laser pulses. In a typical experiment, we average the electrometer signal over 30 laser pulses (3 s) for each delay setting.…”
Section: ■ Experimentsmentioning
confidence: 99%
“…3−7 For example, studies on the photoemission of iodide from aqueous surfaces showed that ionic surfactants attract oppositely charged ions from the bulk to the air−water interface, thereby enhancing the reaction while pushing equally charged ions into the bulk liquid. 7 It has been suggested that electrostatic interactions are key to understanding reactions at interfaces covered by ionic surfactants. An experimental study has shown that the presence of octanoic acid on the surface of an aqueous solution decreases the rate of heterogeneous ozonation of pyrene, whereas the presence of octan-1-ol accelerates it.…”
Section: ■ Introductionmentioning
confidence: 99%
“…41 Several experiments have used ultraviolet photoelectron spectroscopy (UPS) to study the electronic structure of free nanoparticles. [42][43][44][45][46][47][48][49][50][51][52][53] Many of these 107 studies have used a velocity map imaging spectrometer to image a projection the nascent 108 photoelectron distribution of low energy electrons that originated from valence energy 109 5 levels. 42,43,[46][47][48][49][50][51][52][53] Additionally, X-ray photoelectron spectroscopy (XPS) studies have probed free nanoparticles to provide elemental information of the surface.…”
mentioning
confidence: 99%